Adsorption of methyl iodide on reduced silver‐functionalized silica aerogel: Kinetics and modeling. Issue 4 (11th February 2021) - Tang, Siqi; Choi, Seungrag; Nan, Yue; Tavlarides, Lawrence L.
Abstract: The low concentration methyl iodide (CH3 I) adsorption process on reduced silver‐functionalized silica aerogel (Ag 0 ‐Aerogel) was studied. The kinetic data were acquired using a continuous flow adsorption system. Because the corresponding physical process was observed, the shrinking core model (SCM) was modified and applied. An average CH3 I pore diffusivity was calculated, the CH3 I‐Ag 0 ‐Aerogel reaction was identified as a 1.40 order reaction instead of first order reaction, and the n th order reaction rate constant was determined. This modified SCM significantly increases the accuracy of adsorption behavior prediction at low adsorbate concentration. Modeling results indicate that the overall adsorption process is controlled by the pore diffusion. However, at low adsorbate concentration (ppbv level), the CH3 I adsorption is limited to the surface reaction due to the low uptake rate in a predictable time period.